2023
DOI: 10.1088/1572-9494/aceeed
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic effects on anisotropic expansion-free fluid content

Abstract: The major goal of this work is to find solutions of Einstein-Maxwell field equations for anisotropic, expansion-free, non-static, spherically distributed matter content. The analytical models that highlight the major benefit of simplicity are shown and this makes it possible to use them as a toy model to illustrate how cavities evolve. Furthermore, the transport equations, quasi-homologous constraints and the junction conditions are also evaluated along with its useful implications. Eventually, the consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Furthermore, researching stellar structures under modified gravity can provide new insights into processes like as gravitational collapse, neutron star mergers, and the behavior of matter in extreme gravitational fields, eventually improving our understanding of the Universe's complexities. Some of these are f (R) [17][18][19][20], f (G) [21][22][23], f (R, T) [24][25][26][27], f (Q) [28,29], f (R, A) [30][31][32], f (R, f) [33][34][35] and f (R, f, X) [36][37][38] modified gravity theories. In these theories, the equations governing gravity are modified to include additional terms that could explain the observed acceleration of the Universe.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researching stellar structures under modified gravity can provide new insights into processes like as gravitational collapse, neutron star mergers, and the behavior of matter in extreme gravitational fields, eventually improving our understanding of the Universe's complexities. Some of these are f (R) [17][18][19][20], f (G) [21][22][23], f (R, T) [24][25][26][27], f (Q) [28,29], f (R, A) [30][31][32], f (R, f) [33][34][35] and f (R, f, X) [36][37][38] modified gravity theories. In these theories, the equations governing gravity are modified to include additional terms that could explain the observed acceleration of the Universe.…”
Section: Introductionmentioning
confidence: 99%
“…According to their study, the solution behaves properly and the research demonstrated that the solution obtained depicts a stable and physically feasible compact star. There are a few researchers who identified the responsible elements for the irregularity or stability of the compact objects with static and non-static geometries [11,[44][45][46][47][48][49][50]. The relevant quantities of the emergence of inhomogeneity are discussed by Yousaf et al [51] by considering a locally anisotropic composition in ( )  f T , gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Nojiri and Odintsov [17] developed the reconstruction program for the number of modified gravities: scalar-tensor theory, f (R), F (G) and string-inspired, scalar-Gauss-Bonnet gravity and demonstrated that cosmological sequence of matter dominance, deceleration-acceleration transition and acceleration era may always emerge as cosmological solutions of such theory. Elizalde et al [20] examined the proposed unified theory of exponential modified gravity, which accounts for early-time inflation and late-time acceleration, successfully navigating local tests and cosmological bounds, yet revealing instability during the inflationary era, with late-time evolution resembling that of the ΛCDM model for dark energy. Granda [21] investigated unified inflation and late-time accelerated expansion, integrating exponential and R 2 corrections within modified gravity theory, while Dolgov and Kawasaki [22] demonstrated that recent proposals attributing cosmic acceleration to small curvature modification of gravity encounter severe instabilities and conflict with established gravitational interaction properties.…”
mentioning
confidence: 99%